GLOBALNE SIECI KOMPUTEROWE I ICH ROLA W PEDAGOGICE - Paprzycki, Marcin; Mitchel, Tony (Wydawnictwo Naukowe UAM w Poznaniu, 1996)
Recent years have been characterized by a sudden explosion of a new medium - global computer networks. This new medium will not only have a profound effect on the very fabric of the society but also on education. First, we describe the basic tools used to explore the resources of the networks (bbs, ftp, telnet, listserv). Second, we sketch some possible uses of these tools in educational settings.
Keywords: Sieci komputerowe; FTP; Poczta elektroniczna; Grupy dyskusyjne; Czasopisma elektroniczne; Uczenie na odległość; Computer networks; E-mail; Online communications; Electronic papers; E-learning; Neodidagmata